Implementation of Rapid Application Development (RAD) Method for Mobile-Based Ice Cream Ordering Application - Bahari, Ashroff Fazri; Pramudwiatmoko, Arif (Institut Riset dan Publikasi Indonesia, 2025)
Mobile technology has changed the way consumers interact with service and product providers. One of the impacts is the increasing need for online ordering services that offer comfort and convenience. However, many businesses have not utilized mobile technology optimally. This research aims to develop an Android mobile-based ice cream ordering application with a case study on Pak Wagiman's Ice Cream business. There are challenges faced by ice cream businesses, including intense competition, fluctuating demand, accessibility needs, order recording errors, and limited technology adoption. The application development method used is Rapid Application Development (RAD), with stages: needs analysis, system design (use case diagram, class diagram and interface), application development using Kotlin on Android Studio, and MySQL database, and the last stage is black box testing and feasibility testing by users and implementation. Data collection was carried out through a questionnaire to 120 customers using a Likert scale. The results of blackbox testing show that the application's functionality runs perfectly (100%), while the feasibility test gives a score of 95.6% (very feasible). The application proved effective in optimizing business processes, and further development is recommended to add a live chat feature to improve direct interaction with customers.